Revocable and non-invertible multibiometric template protection based on matrix transformation - Jegede, Abayomi; Udzir, Nur Izura; Abdullah, Azizol; Mahmod, Ramlan (Universiti Putra Malaysia Press, 2018)
Biometric authentication refers to the use of measurable characteristics (or features) of the human body to provide secure, reliable and convenient access to a computer system or physical environment. These features (physiological or behavioural) are unique to individual subjects because they are usually obtained directly from their owner's body. Multibiometric authentication systems use a combination of two or more biometric modalities to provide improved performance accuracy without offering adequate protection against security and privacy attacks. This paper proposes a multibiometric matrix transformation based technique, which protects users of multibiometric systems from security and privacy attacks. The results of security and privacy analyses show that the approach provides high-level template security and user privacy compared to previous one-way transformation techniques.